Maternal Separation Induced Visceral Hypersensitivity Evaluated via Novel and Small Size Distention Balloon in Post-weaning Mice - Tao, Enfu; Long, Gao; Yang, Ting; Chen, Bo; Guo, Rui; Ye, Diya; Fang, Marong; Jiang, Mizu (Frontiers in Neuroscience, 2022)
Early life stress (ELS) disposes to functional gastrointestinal diseases in adult, such as irritable bowel syndrome (IBS). Maternal separation (MS) is a well-known animal model of IBS and has been shown to induce visceral hypersensitivity in adult rats and mice. However, to the best of our knowledge, it has not been reported whether MS induces visceral hypersensitivity in young mice, such as the post-weaning mice. Moreover, the method for evaluation of visceral sensitivity also has not been described. Accordingly, the present study aims to evaluate the visceral sensitivity caused by MS in post-weaning mice and develop a novel and small size distention balloon for assessment of visceral sensitivity of such mice. Male pups of C57BL/6 mice were randomly divided into two groups, MS (n = 12) and non-separation (NS) (n = 10). MS pups were separated from the dams through postnatal day (PND) 2 to 14, while NS pups were undisturbed. After, all pups stayed with respective dams and were weaned at PND 22. Visceral sensitivity was evaluated by colorectal distention (CRD) with a novel and small size distention balloon at PND 25. The threshold of abdominal withdrawal reflex (AWR) scores were significantly lower in MS than NS. Additionally, AWR scores at different pressures of CRD were significantly higher in MS than NS. The results demonstrate that MS induced visceral hypersensitivity in post-weaning mice. The designed small size distention balloon for evaluation of visceral sensitivity is of significance to further study the pathophysiology of IBS from early life to adulthood.